2011
DOI: 10.3174/ajnr.a2729
|View full text |Cite
|
Sign up to set email alerts
|

Single-Shot Turbo Spin-Echo Diffusion-Weighted Imaging for Retinoblastoma: Initial Experience

Abstract: BACKGROUND AND PURPOSE:Retinoblastoma may exhibit variable hyperintensities on DWI, resulting in different values in the ADC maps, depending on their histology and cellularity. However, EP-based DWI has susceptibility artifacts and image distortions, which make DWI of the orbit a challenging technique. The aim of this study was to investigate the feasibility of single-shot turbo spin-echo (HASTE) DWI in the evaluation of children with retinoblastoma and to assess the value of ADC maps in differentiating viable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 23 publications
1
28
2
Order By: Relevance
“…[7][8][9][10][11] Previous reports showed variable DWI intensities and ADCs in retinoblastomas, depending on their histology and cellularity. 3 Abdel Razek et al 4 reported that the mean ADC was 0.49 6 0.12 3 10 23 mm 2 s 21 on EP imaging, which is lower than the mean ADC of the present study. They mentioned that the ADC values were significantly lower in their patients with optic nerve invasion.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…[7][8][9][10][11] Previous reports showed variable DWI intensities and ADCs in retinoblastomas, depending on their histology and cellularity. 3 Abdel Razek et al 4 reported that the mean ADC was 0.49 6 0.12 3 10 23 mm 2 s 21 on EP imaging, which is lower than the mean ADC of the present study. They mentioned that the ADC values were significantly lower in their patients with optic nerve invasion.…”
Section: Discussioncontrasting
confidence: 55%
“…2,5 Diffusion-weighted imaging (DWI) is widely used to diagnose tumours, inflammation and vascular disease in both intracranial and extracranial lesions. 3,4,[6][7][8][9][10][11][12][13][14][15][16] Previous studies also revealed the efficacy of DWI to evaluate orbital lesions including orbital tumours of adults 8,9 and children, 10 ocular adnexal lymphomas, 9,11 immunoglobulin G4 (IgG4)-related disease, 9 endophthalmitis 12 and optic nerve lesions. 13,14 However, it is sometimes difficult to evaluate intraorbital structures with echoplanar (EP) imaging, which is the most common imaging technique for DWI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, single-shot turbo spin-echo diffusionweighted imaging could be used when susceptibility artifacts are too strong for EPI-DWI. 26 In addition, view angle tilting could be used with EPI to reduce geometric distortions caused by B 0 inhomogeneity. 27 This work was motivated by the possibility of correcting MRI artifacts induced by orthodontic appliances using permanent magnets with a strong coercivity (Rollins NK, presentation at Philips Pediatric MRI users meeting, January T VIII.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular MRI holds the potential to provide guidance during diagnostic assessment and treatment of ophthalmological diseases [8,[10][11][12][13]. With a sensitivity that is close to that of CT, MRI can serve as a diagnostic tool for eye tumors as well as optic neuropathies such as optic neuritis [14][15][16][17][18][19][20]. Ultimately, the development of ocular MRI applications is aiming at MR image based biometry [21,22] to support advanced intraocular lens implantation or refilling procedures that restore visual function and accommodation [23].…”
Section: Introductionmentioning
confidence: 99%